An efficient dye-fixation technique with reactive dye for a wash-free process of silk fabrics without water discharge. Issue 9 (May 2022) - Zhu, Lei; Pei, Liujun; Wang, Jiping
Coloring textiles with less or without water discharge for sustainable and cleaner production has been a hot topic for a long time due to increasing social, environmental and consumer requirements. In this paper, a new and efficient dye-fixation technique with reactive dye for a wash-free process of silk fabrics without water discharge is presented. Here, decamethylcyclopentasiloxane is employed as the dyeing medium, Reactive Black 5 as the selected dye and sodium carbonate as the alkali. The results show that the dye-fixation rate is higher than 90% and the dyed silk fabrics have good color strength, tensile properties, hand values (including stiffness, softness and smoothness), washing fastness and wet rubbing fastness when adding proper alkali into the dye solution. A probable mechanism was proposed.